2013
DOI: 10.1128/mcb.01019-12
|View full text |Cite|
|
Sign up to set email alerts
|

Arkadia, a Novel SUMO-Targeted Ubiquitin Ligase Involved in PML Degradation

Abstract: bArkadia is a RING domain E3 ubiquitin ligase that activates the transforming growth factor ␤ (TGF-␤) pathway by inducing degradation of the inhibitor SnoN/Ski. Here we show that Arkadia contains three successive SUMO-interacting motifs (SIMs) that mediate noncovalent interaction with poly-SUMO2. We identify the third SIM (VVDL) of Arkadia to be the most relevant one in this interaction. Furthermore, we provide evidence that Arkadia can function as a SUMO-targeted ubiquitin ligase (STUBL) by ubiquitinating SUM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 51 publications
4
95
0
Order By: Relevance
“…Here, we describe the active mechanism for the removal of CenH3 from centromeres. Recent studies have shown that sumoylation, as well as ubiquitination, can be a signal for protein removal from complexes and transference into degradation pathways (32,33). Our results demonstrate that CenH3 is subjected to sumoylation and provide evidence for the CDC48A NPL4 -directed centromere disassembly through active unloading of sumoylated CenH3 from native centromeres.…”
Section: Discussionsupporting
confidence: 54%
“…Here, we describe the active mechanism for the removal of CenH3 from centromeres. Recent studies have shown that sumoylation, as well as ubiquitination, can be a signal for protein removal from complexes and transference into degradation pathways (32,33). Our results demonstrate that CenH3 is subjected to sumoylation and provide evidence for the CDC48A NPL4 -directed centromere disassembly through active unloading of sumoylated CenH3 from native centromeres.…”
Section: Discussionsupporting
confidence: 54%
“…This work echoed our previous finding of the SUMO-targeted ubiquitin ligases (STUbLs) RNF4 and its fission yeast homologs, Rfp1 and Rfp2, all containing multiple SIMs closely positioned as a cluster (14). Sequence gazing on Arkadia has also led to similar findings by other groups (15,16). Among the three Arkadia SIMs, SIM3 is the most critical, and its particular sequence (VVDLT) resembles a VIDLT-type high-affinity SIM (17); SIM1 and SIM3 together contribute to the bulk of SUMO affinity of the entire SBD, and their simultaneous mutation results in complete loss of SUMO binding (13).…”
supporting
confidence: 71%
“…7D). This localization was expected due to the presence of the SIMs, which typically mediate interactions with the highly SUMOylated PML proteins and have been previously reported to target Arkadia to PML NBs (53). The localization of the ⌬S ARKL1 mutant to PML indicates that this mutation did not disrupt interactions with sumoylated proteins, and the data as a whole indicate that the polyserine stretch in ARKL1 mediates an interaction with the CK2␤ KSSR motif.…”
Section: Figmentioning
confidence: 75%
“…While we did not recover Arkadia with WT CK2␤ in our proteomics experiment, this could be due to incompatibility of Arkadia peptides for mass spectrometry (due to unusual sizes or composition) or due to low levels of Arkadia in the cell. In support of the latter possibility, Arkadia is known to be a very unstable protein, which is likely due to its autoubiquitylation (53,71). Arkadia has been reported to have multiple functions, including transforming growth factor ␤ (TGF-␤) signaling and DNA damage responses, and can also induce PML degradation in response to arsenic trioxide, which causes hyper-SUMOylation of PML (53,(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%